The Effect of Internal and External Lean Practices on Performance: A Firm-Centered Approach - Chanegrih, Tarek; Creusier, Jordane (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2016)
The aim of this paper is to enhance the understanding of the relationship between lean practices and both operational and financial performance. A sample of 171 French manufacturing firms shows a direct effect of external lean practices on financial performance. A firm-centered approach identified three profiles. “Full achievers” present significant differences in both operational and financial performance compare to “weak achievers”. Even if the difference in operational performance is significant between “full achievers” and “internal lean dominant”, there is not a significant difference in financial performance.